Música e tecnologia na escola: diretrizes pedagógicas para os anos iniciais do ensino fundamental guiadas pela bncc - Carvalho, Tereza Cristina Dourado Carrah Vieira (2022)
The teaching of musical language in the early years of fundamental education in Brazilian basic education, together with the use of digital information and communication technologies (DICT) has been investigated as a strategy that can favor the teaching and learning processes at school. However, it is necessary for the teacher to adopt a methodology that contextualizes them and that can be guided by pedagogical guidelines maintained as a didactic component in the promotion of activities in the area of music with DICT. Thus, this research had the general objective of investigating, in the light of interactional ethnography, the experimental experiences in the “Music and Technology at School Project”, during remote teaching, at the Professora Francisca Florência da Silva Elementary School, with a view to elaborating of pedagogical guidelines for teaching musical language with digital technologies aspired to by the Brazilian National Common Curricular Base - BNCC. Therefore, it sought to: analyze, from an emic perspective, the experiences developed in the project, listing learning objectives, contents, instructional methodological strategies, digital resources and evaluation procedures, which support the teaching of musical language mediated by DICT during teaching remote; identify the expressive cases of the research in search of pedagogical practices experienced during the project, which are commonly invisible, and, finally, propose pedagogical guidelines for teaching musical language with digital technologies, guided by the BNCC, based on the results related to the experiences of the project , to be organized in an e-book aimed at teachers in the early years of elementary school. The research, with an ethnographic approach, aimed to understand the universe of the subjects and the context of the project, adopting: a bibliographical and documental review, participant observation, applications of online interviews and interviews, descriptive systems and technological records (audiovisual and photographic). Data analysis was based on a contrastive analysis from these different data sources, in order to construct or conceptually report the cultural phenomena under study. Finally, the results identified the second and fourth classes as expressive cases in which they allowed the development of pedagogical practices, digital resources and instructional methodological strategies, which were organized in accordance with the BNCC guidelines and served as a reference for the development of a proposal with pedagogical guidelines that were released in an e-book.